Non-Lactobacillus-Dominated Vaginal Microbiota Is Associated With a Tubal Pregnancy in Symptomatic Chinese Women in the Early Stage of Pregnancy: A Nested Case–Control Study - Ruan, Xiao-Feng; Zhang, Ying-Xuan; Chen, Si; Liu, Xiao-Rong; Zhu, Fang-Fang; Huang, Yan-Xi; Liu, Xiao-Jing; Luo, Song-Ping; Deng, Gao-Pi; Gao, Jie (Frontiers in Cellular and Infection Microbiology, 2021)
Microbiota can affect woman physiology, meanwhile woman physiology can affect the vaginal microbiota composition and function. The features of vaginal microbial community can reflect the health condition of woman, and they are well on the way to become new biomarkers for diagnosis of disease. During pregnancy, the Lactobacillus dominated is regarded as a keystone in the vaginal microbial community, for it stabilize the vaginal microbiota by producing antimicrobial compounds and competing adhesion. An altered vaginal microbial composition provides a marker for adverse pregnancy outcomes. This nested case-control study aims to characterize the vaginal microbiota in tubal pregnancy among women presnting with pain and / or uterine bleeding in early pregnancy. Women with a symptomatic early pregnancy of unknown location in The First Affiliated Hospital of Guangzhou University of Chinese Medicine in Guangzhou were included in this study. 16S rDNA gene sequencing of the V3-V4 variable regions has been performed to assess the vaginal microbial community diversity and structures, taxonomic biomarkers, microbiota classification. The primary outcome is early pregnancy locations. The study results show that vaginal microbial community in tubal pregnancy showed higher diversity (PD-whole-tree, median: 8.3 vs 7.1, P < 0.01; Shannon diversity index, median: 1.43 vs 0.99, P = 0.047), different structures were shown between two pregnancy locations (R = 0.23, P < 0.01). Genus Lactobacillus was significantly enriched in intrauterine pregnancy, while genus Gardnerella and genus Prevotella were significantly enriched in tubal pregnancy. Lactobacillus abundance could classify the pregnancy location commendably (AUC = 0.81). Non-Lactobacillus dominated microbiota (≤ 85% Lactobacillus) was significant associated with tubal pregnancy (adjusted odds ratio: 4.42, 95% confidence interval: 1.33 to 14.71, P < 0.01). In conclusion, among women with symptomatic early pregnancies, a higher diversity and less abundance of Lactobacillus vaginal microbial community composition was associated with tubal pregnancy.